PERANCANGAN KEY PERFORMANCE INDICATOR PADA DEPARTEMEN MAINTENANCE DENGAN PENDEKATAN BALANCE SCORECARD DI PT XYZ - Hamada Aulia (2021)
Performance measurement is an important part of achieving company goals, so we need a method that can guarantee the achievement of company strategy. The maintenance department at the company has carried out performance appraisals using only one Critical Equipment Availability measurement tool. In this phenomenon, the department has not been able to represent the performance design so that there needs to be another measure in the maintenance department to be able to provide an assessment that supports the achievement of the department's strategy. Accordingly, it is necessary to develop a maintenance department performance measurement using the Balanced Scorecard and ANP methods. This study aims to assist in the design process of key performance indicators in the maintenance department. In this study, the cut-off point method is used to eliminate key performance indicators, which previously had 50 key performance indicators into 27 key performance indicators, then to the balanced scorecard stage which will classify key performance indicators into four balanced scorecard perspectives, namely financial, customer, internal business and learning. and the last stage of growth is weighting these criteria with the ANP method. The input parameter is the pairwise comparison between the key performance indicators. The results show that the proposed method can build a key performance indicator design in the maintenance department From the research, it was obtained the criteria weight value where the learning and growth perspective had the highest value of 0.31, followed by the customer perspective with a weighting result, namely with a value of 0.28, while internal business with a value of 0.24 and finally the financial perspective with a value of 0.16. Keywords: key performance indicator,ANP,Cut off Point, Balanced Scorecard.